Análise morfotectônica do Planalto Ocidental Paulista, ao sul do Rio Tietê: indicadores de deformações neotectônicas na fisiografia da paisagem - Guedes, Ivan Claudio [UNESP] (2014)
The Western Plateau of São Paulo presents a grievous framework of accelerated erosion, arising from the unbridled occupation and soil intensive use combined with the natural fragility of the terrain. The aim of this thesis is to evaluate the hypothesis that tectonic factors have controlled part of alterations in the landscape and have contributed to the worsening of the erosion processes that are reflected in siltation of drainage channels and the opening of ravines and gullies as well as its influence on settings of relief in this part of São Paulo’s territory. It is understood that the watersheds and the conformation of drainages which compound the study area reflect structural blocks controlled by tectonic activity and suffer processes of intraplate efforts, resulting in deformation of the fluvial morphometry and incidence of erosive and depositional processes. The analysis of neotectonic frame was performed by the application of fluvial morphometric information and geological and geomorphological data. The studies are about the longitudinal profiles of the drainages, the application of SGI “Stream-Gradient Index (slope x length)” and the nickpoint identification of the main tools employed. Nevertheless, the lineament analysis of drainages and relief were also applied to the area of study, wherein was possible to check the directions of structures and to infer the structural blocks, and record of paleoseismics information, from the identification of liquefaction structures. The Western Plateau of São Paulo is seated on Cretaceous rocks of the Bauru and Caiuá groups and Cenozoic sediments. It is understood that the landscape evolution, in the Quaternary, in this part of São Paulo territory, has been tightly influenced by deformations imposed by seismic forces, where the rising of a morphostructural block leads to removal of pedogenic coverage, generating shallow soils, and subsistence of an adjacent block which provides, in...